Does exclusive enteral nutrition reduce the rate of stoma formation in patients requiring ileocolic resection for Crohn's disease? A single center experience. (August 2021) - Gordon–Dixon, Ayeshah; Hampal, Rumneek; Miah, Anur; Webb–Butler, Shruti; Lewis, Wendy; Ross, Rose; Ghosh, Nivedita; Grimes, Caris
Summary: Background and aim: Nutrition has a role in achieving and maintaining remission in Crohn's disease. The aim of this study was to determine the impact of a strategy of steroid-avoidance and Exclusive Enteral Nutrition (EEN) for 6 weeks (with a minimum of 4 weeks) in adult patients presenting with acute small bowel Crohn's disease followed by an interval ileocolic resection 4–6 weeks later. Methods: Retrospective review of prospectively collected data. Patients were administered exclusive enteral nutrition (EEN) for at least 4 weeks prior to surgery. Results: 24 EEN patients included. Median age of 45 (range 23–73). 17/24 patients tolerated Modulen for at least 4 weeks, 5 were switched to Ensures and 2 a liquid diet. 6 patients underwent surgery earlier than planned. Prior to surgery, there was no change in the mean BMI, albumin increased from a mean of 36 g/L (range 25–43) to 40 g/L (range 30–48). CRP levels decreased by a mean of 35.8 mg/L overall. 19 (79%) of operations were performed laparoscopically. 6 of the cases were re-do operations. All but 3 patients avoided a stoma at the time of the original operation. There were 5 post-operative complications: 1 anastomotic leak in a patient with a BMI of 42, 3 cases of paralytic ileus and 2 wound infections. Median length of stay was 7 days (range 3–76 days). Only 2 patients were readmitted within the 30-day post-operative period. Conclusion: The pre-operative use of EEN appears to avoid unnecessary stoma formation with acceptable clinical outcomes.